2008
DOI: 10.1099/jmm.0.47721-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anaplasma phagocytophilum and its coinfection with Borrelia afzelii in Ixodes ricinus and Ixodes persulcatus ticks inhabiting Tver Province (Russia) – a sympatric region for both tick species

Abstract: Human granulocytic anaplasmosis (HGA) and Lyme borreliosis (LB) are tick-borne infectious diseases caused by Anaplasma phagocytophilum and Borrelia burgdorferi sensu lato species, respectively. In this study, p44/msp2 paralogues specific to A. phagocytophilum and 5S-23S rRNA gene-intergenic spacers specific to B. burgdorferi sensu lato species were detected by PCR in ticks collected in two regions, Tver (Kalinin) and Konakovo, of the Tver (Kalinin) Province located 150 km north-west of Moscow. The PCR amplicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…However, A. phagocytophilum has previously been reported simultaneously in I. persulcatus and I. ricinus at geographical sites where the two tick species are distributed. Moreover, sequences of the A. phagocytophilum p44/msp2 gene indicated that there are no differences between sequences derived from I. ricinus and I. persulcatus [23]. In Estonia, even at two sites in south‐eastern Estonia, where both species of ticks co‐circulate and I. ricinus constitutes the minority (10–20%) of the tick population, we found A. phagocytophilum only in I. ricinus ; thus, the role of I. persulcatus for the circulation of A. phagocytophilum in Estonia is unclear and further tick collections are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…However, A. phagocytophilum has previously been reported simultaneously in I. persulcatus and I. ricinus at geographical sites where the two tick species are distributed. Moreover, sequences of the A. phagocytophilum p44/msp2 gene indicated that there are no differences between sequences derived from I. ricinus and I. persulcatus [23]. In Estonia, even at two sites in south‐eastern Estonia, where both species of ticks co‐circulate and I. ricinus constitutes the minority (10–20%) of the tick population, we found A. phagocytophilum only in I. ricinus ; thus, the role of I. persulcatus for the circulation of A. phagocytophilum in Estonia is unclear and further tick collections are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…I. persulcatus ticks inhabiting the Far East were shown to be infected by the same Anaplasmataceae bacteria -Anaplasma phagocytophilum, E. muris, and 'Candidatus Neoehrlichia mikurensis' -as I. persulcatus in other parts of their distributive area (Eremeeva et al, 2006;Shpynov et al, 2006;Masuzawa et al, 2008;Rar et al, 2010). In addition, a new genetic variant of Anaplasma bovis was found in H. concinna ticks, and two distinct Ehrlichia genetic variants were found, namely Ehrlichia sp.…”
Section: Introductionmentioning
confidence: 97%
“…Although Ixodes ticks often feed on white-tailed deer, the deer are infected with the Ap-Variant 1 strain of A. phagocytophilum, rather than with the human strain, in the United States (146). Diverse A. phagocytophilum strains are also found in animals and ticks in Europe, Japan, and Russia (109,111,151,160,170,203,238,239), where HGA has been rarely reported. These findings imply that the zoonosis potential of A. phagocytophilum depends not only on the transmissibility, habitats, and population density of ticks and infected mammals (90) but also on the genetic variations of A. phagocytophilum.…”
Section: Morphologymentioning
confidence: 99%